Public’s perception about religious development through social activities in Bangunsari village, Pacitan - Malta Anantyasari; Ezif Rizqi Imtihana (Journal of Interdisciplinary Islamic Studies, 2022)
Social activities the form of service activities directly related to community interests. This research was conducted to find out 1) the form of social activities carried out in developing religious activities in Bangunsari village, 2) public perceptions about social activities carried out. This research is survey research conducted in Bangunsari village, Bandar Pacitan district. Data was collected using questionnaires and interviews. Data analysis was carried out in qualitative descriptive. Research results showed that 1) there were 3 types of social activities in developing religious activities in Bangunsari village, there are donations for mosque construction, religious education and da'wah or recitation, 2) public perception shows that the socio-religious activities carried out received a positive response from the community in Bangunsari village.